Australia and New Zealand - Lindop, Christine (Oxford University Press, 2008)
What do you find in these two countries at the end of the world? One is an enormous island, where only twenty million people live - and the other is two long, narrow islands, with ten sheep for every person. One country has the biggest rock in all the world, and a town where everybody lives under the ground; the other has a beach where you can sit beside the sea in a pool of hot water, and lakes that are bright yellow, green, and blue. Open this book and start your journey - to two countries where something strange, beautiful or surprising waits around every corner